Efektivitas Karbon Aktif Dari Batu Bara Muda dalam Menurunkan COD pada Air Limbah Industri Tahu - Febri Juita Anggraini; Arsapita, Rara; Yasdi, Yasdi (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Lignite is the lowest quality coal and cannot be traded in the market. One alternative is that lignite coal has a better use value, lignite coal can be used as a material for making activated carbon. Coal which has become activated carbon can be applied to tofu industrial waste water as an adsorbent in absorbing chemical oxygen demand contained in tofu industrial waste water. The purpose of this study was to determine the characteristics of activated carbon from lignite,opium conditions and isotherm modeling. The method used in the manufacture of activated carbon from lignite is to use an activator in the form of 2 M NaOH with a carbonization temperature of 500°C using variations of 60 minutes and 90 minutes, then the activated carbon is soaked in 2 M HCl solution. Results from carbon characteristics The active lignite coal meets the requirements of SNI 06-3730-1995, the optimum time for reducing COD is 15 minutes with %removal of 66%, the optimum pH for reducing COD is pH 5 with %removal of 63.84% and the isotherm model follows the Harkin isotherm model - Jura with an average relative error of 13.024.